Influence of interlocking dowels on motor core loss. Issue 2 (7th March 2016) - Zhou, Gui-Yu; Hao, He; Jin, Meng-Jia; Shen, Jian-Xin
Abstract : Purpose: – The purpose of this paper is to investigate the effect of the interlocking process on the iron loss in the lamination core and to increase the efficiency of electrical machines. Design/methodology/approach: – A 3D electromagnetic model of the interlocking dowels is proposed in order to simulate the eddy current distribution in the lamination core. Considering the time-consuming of the 3D finite element method (FEM), a 2D electromagnetic model is then proposed based on the 3D model. Influence of the interlocking process on the motor performances is analyzed with 2D FEM, considering the electrical connection of the dowels and the magnetic property deterioration of the electrical steel sheets. Findings: – The interlocking process removes the insulation between the laminations at the cut-edges of the interlocking dowels, causing extra eddy current loss in the lamination core. The effect of the interlocking process is dependent on the number, location and size of the interlocking dowels. Practical implications: – The interlocking dowel model is established in order to simulate the effects of the interlocking process. By using the FEM calculation, optimal solution is discussed to minimize the undesired effect of the interlocking dowels. Originality/value: – In this paper, the FEM model of the induction motor with interlocked stator core is first established, then simulation analysis is implemented. Results shows that choosing a proper number of interlocking dowels with suitable location and size can reduce the extra loss.